The Future Possible Distribution of Kasnak Oak (Quercus vulcanica Boiss. & Heldr. ex Kotschy) in Anatolia under Climate Change Scenarios - Özcan, Ali Uğur; Gülçin, Derya; Tuttu, Gamze; Velázquez, Javier; Ayan, Sezgin; Stephan, Jean; Tuttu, Uğur; Varlı, Ahmet; Çiçek, Kerim (MDPI AG, 2024)
The deterioration of natural habitats for oak species has steadily occurred as a consequence of both climate change and human pressure. Therefore, detailed and reliable information about the geographic distribution of oak species under changing climate conditions is needed for diverse ecological and conservation practices. This study examined the habitat suitability of endemic Kasnak oak, Quercus vulcanica Boiss. & Heldr. ex Kotschy, an endemic that ranges across the Central Anatolia Region and surrounding mountains in Türkiye. The occurrence data were gathered through fieldwork, and new records were identified. Next, we applied ecological niche modeling to assess the past, present-day, and future potential geographic range of the species in Anatolia. Projections for the Last Glacial Maximum indicate that most of the suitable areas for Kasnak oak were in southern Anatolia. However, present-day estimates suggest projections estimate suitable habitats in northern Anatolia and around the Anatolian Diagonal. According to future projections, the distribution of the species seems to decrease by 2100, with habitat suitability reduction ranging from 3.27% to 7.88%. Projections suggest a decrease in habitat suitability for the species, particularly in the western and southern Türkiye in the future. Moreover, the projections indicated that suitable habitats for the northern range of the species would likely persist until 2100, although they would diminish towards the northeast. The results can be effectively applied to enhance biodiversity conservation planning and management, leading to the development of innovative strategies.